Some aspects on the Pictures of the North - Pettersson, Lennart (Nordlit, 2008)
The objectives of this article are to draw the attention to, in my view, two necessities in the field of research on illustrated travel literature. I will argue that in order to understand the nature of illustrated travel literature the research has to be multidisciplinary and has to deal with the written text as well as the illustrations. The reader gained their perceptions of the places described from both pictures and texts and in order to retrieve how different parts of the world were, and still is, perceived according to certain criteria stated in travel literature, scholars must work with a variety of visual and textual communication strategies. The second of my "necessities" is that this material urges scholars to study it with quantitative methods. There are so many different illustrated travel books that it would be a loss if researcher did not try to study them as one unit and thereby gain generalized knowledge on the field. Having stated these two "necessities" I must also state that I do not mean that all research into travel literature must have these approaches but I hope that they will be important factors in the discourses the coming years. In order to show some of the possibilities of the methods mentioned above I will discuss some of the possible aspects of a quantitative study of the pictures of the north as they appear in illustrated travel literature of the nineteenth century. I will present statistics dealing with artistic subjects, differences between the patterns of illustrations in books published in different languages and how the pictorial revolution in the 19th century changed the travel literature. In the second part of the article I will examine one illustrated travel book in order to high-light how text and illustration complemented each other and created significance together.